Incidencia de brucelosis bovina (Brucella abortus) en la provincia de Santo Domingo de los Tsachilas. - Vera Espinel, Northon Vladimir (2013)
This research was conducted in the Laboratory of Biotechnology, State Technical University Quevedo. The overall objective of this research was to determine the prevalence of bovine brucellosis in the province of Santo Domingo de los Tsachilas using the Rose Bengal test and PCR confirmation. This study was done to check the technique chain reaction (PCR) of the sample that came serologically positive with Rose Bengal (RB) in the diagnosis of bovine brucellosis. A total of 400 blood samples were collected from 43 herds in the province of Santo Domingo de los Tsachilas with high historical prevalence of brucellosis. An average of 29% tested positive for the analysis of RB, meanwhile that PCR was 25%, in relation to the prevalence of bovine brucellosis according to the prevalence of brucellosis source by source as follows: the parishes Valle Hermoso and Alluriquin with 1% positive cases in each area and the effort, and Santa Maria del Toachi case with 1.5% in each sector, with 2% American Light case, La Concordia with 3% positive cases, 9% Puerto Limon positive cases and San Jacinto Búa 10% cases. The analysis by nonparametric c2 determined statistical significance (P = 0.05). Positive samples amplified a fragment of 725pb. This work suggests that the PCR is a highly efficient and useful for the diagnosis of brucellosis in cattle. It was determined that the economic losses produced in diseased cows is $ 886 U.S. dollars.